PERANAN MODEL HIDRAULIKA DALAM PERENCANAAN PLTGU CILEGON - Siti Umi Kalsum (Universitas Batanghari Jambi, 2015)
In the water works many problems can not be solved with available formulas. This is because the equations were derived from a certain condition that is not necessarily the same situation with the conditions of the planned the water works. Therefore, the hydraulic modeling is very useful. PLTGU Cilegon has several problems, among others: 1. in the event of high sea waves in the Java Sea, the sea water entering through the in take and can cause damage to the blade mixer behind the trash rack; 2. Trash and sediment sucked into thein take until the base so that it can inter fere with the performance of the cooling system. To overcome these problems several alternatives proposed by the pond wave absorbers.The first alternative (addressing sediment and litter) is performed with an entrance aperture variations to determine the water leveland wave in the channel. The second alternative is to be made baffles channel, where the channel baffles makes natural variation door openings. The third alternative is to regulate the water level and wave into the channel by increasing the dimensions of the channel.The results of the simulation in the laboratory, baffle channel before the in take tract with the door dimensional variation sand water level setting and the waves can be used so that thein take tract waves, sediment and trash can be overcome.Keyword: hydraulic modelling,PLTGU Cilegon, the channelbaffles